Accessing the inaccessible: Engaging male-dominated workplaces in alcohol and drug intervention programs. - Cameron, J.; Pidd, K.; Lee, Nicole; Roche, A. (Wiley-Blackwell Publishing Ltd., 2015)
Introduction: Risky alcohol use is associated with a range of adverse social and health outcomes. Research indicates the majority of risky drinkers are employed and suggests that workplace interventions can have positive benefits on alcohol and drug (AOD) use behaviours and attitudes. However, engaging male dominated workplaces to implement alcohol and other workplace health intervention programs is difficult. Approach: As part of a three year quasi-experimental RCT undertaken to implement a workplace AOD program, a qualitative examination of employers’ views about potential barriers and enablers to implementing the program was completed. Face-to-face-interviews and site observations were undertaken with forty-five employees, team leaders and managers, across four different workplaces. Interviews and site observation data were subject to thematic and content analyses to identify consistent features that might influence workplace policy and culture. Key Findings: We identified five broad themes regarding the successful implementation of AOD intervention programs 1) embedding alcohol and drug issues within a broader context of health 2) promoting the value of the program, 3) responsiveness to immediate need, 4) raising awareness of local area resources and 5) sustainability. Our findings indicate that successful intervention programs need to be adaptable and responsive utilising existing workplace processes to enhance capacity and ensure sustainability.Discussions and Conclusions: While research suggests workplace interventions can be effective, they can be very difficult to implement and maintain. However, a number of strategies can be used to improve implementation of AOD intervention programs in workplace settings, especially those targeting high-risk groups such as male dominated workplaces. Implications for Practice or Policy: This study presents a unique opportunity to explore the unique characteristics, behaviours and attitudes toward AOD intervention programs among male-dominated workplaces. There is little research being done in this area and to our knowledge this is the first study of its kind in Australia.